Responsiveness of Nurse Practitioner and Health Personnel in Primary Care Units in Phra Nakhon Si Ayutthaya Province - Leethochawalit, Chokchai (Journal of Health Science of Thailand, 2018)
Beyond the lack of medical doctors situation in Phra Nakhon Si Ayutthaya Provincial Health Office, primary care units in Phra Nakhon Si Ayutthaya have been developed in order to be the first gate of good care in community. PCUs has been operated for 4-5 years by a well trained nurse practitioner (NP) and other health personnel. The objective of positioning the NPs in each PCU was that the good human and communication skills would strengthen services and health education within their communities. This study was aimed at evaluating and compare the responsiveness of the NP as care provider and the other health personnel in the PCUs. In all, 215 PCU care receivers from 16 PCUs in 8 districts in Changwat Phra Nakhon Si Ayutthaya were selected up by systemic random sampling and to be interviewed. WHO responsiveness questionaires were used for exit interviews within 10 official days (Oct. 16-30, 2007) . The study revealed that the responsiveness score of the NPs were higher than that of the health personnel with significant difference at level 0.05 (p < 0.05). Especially in the aspect of trust in care providers and health care structure, autonomy/confidentially and good communication in consulting room. Based on the findings of this study, the NPs should be in every PCU. The PCU team work should developed their competency in term of a polyvalent team in order to support each other so that the PCU can provide more efficient family medical care.